The implementation of innovation by a multinational operating in two different environments: a comparative study - Zain, Mohamed; Richardson, Stanley; Adam, Mohd Nazri Khan (Wiley, 2002)
The aim of the paper is to examine the innovation initiatives and processes followed by two subsidiaries of a German multinational company operating in Europe and Asia and to compare the innovativeness of their operations in these two locations. The study examined the innovation processes followed by the two subsidiary firms operating in Germany and Malaysia, the actual problems faced by them, the critical success factors involved in the implementation, and the work climates of the firms. Interestingly, it was found that both firms followed similar innovation processes. Nevertheless, different types of problems and critical success factors were applicable to both firms. The results showed that the Malaysian subsidiary faced more behavioural problems while the German subsidiary encountered more technical problems. Further, the study showed that a lack of knowledge was the common problem faced equally by both firms. The study demonstrated that the German subsidiary had better working climate compared to its counterpart in Malaysia. Finally, the German subsidiary was found to be more innovation-active than the Malaysian subsidiary as it introduced more types of innovation, interacted with more types of entity in the external environment and introduced more types of training.